Electromagnetic Functions Modulation of Recycled By-Products by Heterodimensional Structure - Ze Nan; Wei Wei; Zhenhua Lin; Ruimei Yuan; Miao Zhang; Jincheng Zhang; Jianyong Ouyang; Jingjing Chang; Hejun Li; Yue Hao (Nano-Micro Letters)
Highlights Turning trash into treasure: The outstanding tunable aerogels were fabricated via heterodimensional by-products of silver nanowires. The first tunable form, aerogel film, shields electromagnetic interference (EMI SE > 89 dB), while the second tunable form, aerogel foam, performs dual EM functions (EMI SE > 30 dB and RL < -35 dB, EAB > 6.7 GHz). Recycle again: The secondary recycled aerogels retain nearly all of their EM protection qualities, making this closed-loop cycle desirable.